2014
DOI: 10.1161/circoutcomes.113.000376
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Testing Before Lower Extremity Amputation Among Medicare Beneficiaries, 2000 to 2010

Abstract: Background-Despite mild reductions in rates of lower extremity amputation over the past decade, few data exist on the use of arterial testing in patients before amputation. Methods and Results-Using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 30 publications
3
26
1
1
Order By: Relevance
“…A Medicare claims based report showed that the rate of any pre-amputation arterial testing (Doppler measurement, vascular imaging) was 68.4%. 45 Although no Hungarian or European data are available for comparison, this single observation cautions against over-interpretation of the primary amputation rate.…”
Section: Discussionmentioning
confidence: 92%
“…A Medicare claims based report showed that the rate of any pre-amputation arterial testing (Doppler measurement, vascular imaging) was 68.4%. 45 Although no Hungarian or European data are available for comparison, this single observation cautions against over-interpretation of the primary amputation rate.…”
Section: Discussionmentioning
confidence: 92%
“…The overall revascularization rates in this cohort (77%) are lower than in the CRITISCH registry; these differences may be explained by a wider inclusion of all hospitals, as opposed to tertiary vascular centers. Medicare-based studies have also shown that a significant percentage of patients do not undergo lower extremity testing with ABIs or imaging prior to major amputation; it is possible that some patients in this cohort were not recognized clinically as having CLI, and were, therefore, not offered revascularization 20 . Importantly, studies of the regional intensity of revascularization rates have suggested that increased rates of revascularization are associated with low rates of major amputation 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in the US amputation was the first choice of treatment in as many as 67% of patients with CLI. In 31.8-50% of patients with CLI, leg amputation was undergone without earlier diagnostic procedures which might otherwise have shown the potential of revascularization [17]. For example, arteriography was performed in 16% of them, ABI was measured in 35% of patients, and only 26% of patients were consulted by a cardiologist and 21% by a vascular surgeon.…”
Section: Discussionmentioning
confidence: 99%